Young stellar object jet models: From theory to synthetic observations - Teșileanu, O.; Matsakos, T.; Massaglia, S.; Trussoni, E.; Mignone, A.; Vlahakis, N.; Tsinganos, K.; Stute, M.; Cayatte, V.; Sauty, C.; Stehlé, C.; Chièze, J. -P. (2014)
Context. Astronomical observations, analytical solutions, and numerical simulations have provided the building blocks to formulate the current theory of young stellar object jets. Although each approach has made great progress independently, it is only during the past decade that significant efforts have been made to bring the separate pieces together. Aims: Building on previous work that combined analytical solutions and numerical simulations, we apply a sophisticated cooling function to incorporate optically thin energy losses in the dynamics. On one hand, this allows a self-consistent treatment of the jet evolution, and on the other hand, it provides the necessary data to generate synthetic emission maps. Methods: Firstly, analytical disk and stellar outflow solutions are properly combined to initialize numerical two-component jet models inside the computational box. Secondly, magneto-hydrodynamical simulations are performed in 2.5D, correctly following the ionization and recombination of a maximum of 29 ions. Finally, the outputs are post-processed to produce artificial observational data. Results: The values for the density, temperature, and velocity that the simulations provide along the axis are within the typical range of protostellar outflows. Moreover, the synthetic emission maps of the doublets [O i], [N ii], and [S ii] outline a well-collimated and knot-structured jet, which is surrounded by a less dense and slower wind that is not observable in these lines. The jet is found to have a small opening angle and a radius that is also comparable to observations. Conclusions: The first two-component jet simulations, based on analytical models, that include ionization and optically thin radiation losses demonstrate promising results for modeling specific young stellar object outflows. The generation of synthetic emission maps provides the link to observations, as well as the necessary feedback for further improvement of the available models.
Keywords: Astrophysics - Solar and Stellar Astrophysics; ISM: jets and outflows; magnetohydrodynamics (MHD); methods: numerical; stars: evolution